Ruthless : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2011)
Hanna, Spencer, Emily and Aria are trying to move on and forget about their old friend Alison DiLaurentis and all the torture she put them through, but someone is trying to keep her spirit alive.
Keywords: Friendship -- Fiction; Secrets -- Fiction; Conduct of life -- Fiction; High schools -- Fiction